Status and Trend of Regal Fritillary (Speyeria idalia) (Lepidoptera: Nymphalidae) in the 4th of July Butterfly Count Program in 1977–2014 - Scott R. Swengel; Ann B. Swengel (Scientifica)
Regal Fritillary (Speyeria idalia) primarily inhabits prairie, a native grassland of central North America, and occurs rarely in nonprairie grasslands further east. This butterfly has experienced widespread decline and marked range contraction. We analyze Regal Fritillary incidence and abundance during 1977–2014 in 4th of July Butterfly Counts, an annual census of butterflies in North America. Volunteers count within the same 24 km diameter circle each year. Only 6% of counts in range reported a Regal, while 18% of counts in core range in the Midwest and Great Plains did. 99.9% of Regal individuals occurred in core range. Only four circles east of core range reported this species, and only during the first half of the study period. All individuals reported west of its main range occurred in two circles in Colorado in the second half of the study. The number of counts per year and survey effort per count increased during the study. During 1991–2014, >31 counts occurred per year in core Regal range, compared to 0–23 during 1975–1990. During 1991–2014, all measures of Regal presence and abundance declined, most significantly. These results agree with other sources that Regal Fritillary has contracted its range and declined in abundance.